Предмет:
МатематикаАвтор:
анонимРешим уравнение:
1) (2х - 3)^2 = 3131 - 2x;
4х^2 - 12х + 9 = 3131 - 2x;
4х^2 - 12х + 9 - 3131 + 2x = 0;
4x^2 - 10x - 3122 = 0;
D = b^2 - 4ac = 100 + 49952 = 50052;
x = (-b ± √D)/2a = (10 ± 2√12513)/8 = (5 ± √12513)/4.
2) 11x - 19 * (x + 1)^2 = 3131 - 2x;
11x - 19x^2 - 38x - 19 = 3131 - 2x;
-17x^2 - 27x - 3150 = 0;
D = 729 + 214200 = 214929;
x = (27 ± 3√23881)/(-34).
3) 7918 - 2* (x + 2)^2 = 3131 - 2x;
7918 - 2 * (x^2 + 4x + 4) = 3131 - 2x;
7918 - 2x^2 + 8x - 8 - 3131 + 2x = 0;
-2x^2 + 10x + 4779 = 0;
D = 100 + 38232 = 38332;
x = (-10 ± 2√9583)/(-4) = (-5 ± √9583)/(-2).
Автор:
emmettniuoДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть